METHODOLOGICAL PRINCIPLES OF HISTORY TEACHING IN PROFESSIONAL EDUCATIONAL INSTITUTIONS - Saodat Abdurashidovna Toshtemirova (European Science Publishing, 2024)
The article presents the requirements for the content of history teaching in professional educational institutions, the legal and normative basis of history teaching, the analyzes and approaches of the specific methodological basis of teaching. Foreign models of history education are analyzed, the need to implement innovative approaches specific to the education system of our country is justified.
Keywords: educational system, professional education, history education, historical consciousness, motivation, competence, innovative technologies, educational content, educational programs, educational process, methodological foundations.